Ochrona danych osobowych w rachunkowości - Durbajło-Mrowiec, Małgorzata (E-Wydawnictwo. Prawnicza i Ekonomiczna Biblioteka Cyfrowa. Wydział Prawa, Administracji i Ekonomii Uniwersytetu Wrocławskiego, 2018)
From 25th May 2018 all the members of European Union were committed to the General Data Protection Regulation (EU) 2016/679 from 27th April 2016 on data protection and privacy for all individuals, free flow of such data and on superseding the Data Protection Directive 95/46/EC to normalize standards on personal data protection. Accountancy led by internal units of an entity or by accounting offices must be adjusted to new requirements. More requirements must be met by accounting offices than by accounting departments which are internal parts of entities-administrators of personal data. Accounting offices are obliged to fulfil requirements of personal data administrators and processing entity. Internal accounting departments will be obliged to fulfil the requirements of the whole entity in the area of composing entrustment agreement, managing personal data processing etc. Accounting departments will not forward informative provisions to a person whose data will be processed by a data administrator.
Keywords: personal data protection; accounting offices; accountancy